Pulmonary Hypertension in Patent Ductus Arteriosus: Correlation with Ductal Size - A Single Center Experience - A N M Tanvir Chowdhury; Md Kashid Omar; Ayasha Sultana; Shanjeeda Shormin; Mir Mosharof Hossain; Md Gaosul Azam; Shaharia Sharmin; Rebeka Akhter Rupa (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Patent Ductus Arteriosus (PDA) remains one of the most common congenital heart defects, particularly affecting neonates and preterm infants. The persistence of a ductal connection beyond the neonatal period can lead to significant clinical consequences, particularly Pulmonary Hypertension (PH) which complicates the hemodynamic profile of the affected patient. This study was conducted to elucidate the correlation between the size of the PDA and the severity of pulmonary hypertension in pediatric patients. A total of 260 children diagnosed with PDA were evaluated in a single tertiary care center using echocardiographic techniques. The majority of the cohort exhibited signs of PH, particularly in cases where the ductus was classified as moderate to large. Our analysis revealed a strong correlation between the size of the PDA and the degree of PH as measured by pulmonary artery pressures. These findings underscore the importance of early identification and management of hemodynamically significant PDA to prevent irreversible vascular changes and complications. To evaluate the relationship between PDA size and the severity of PH using echocardiographic parameters. Materials and methods: A cross-sectional study involving 260 children diagnosed with PDA. Patients were categorized by ductal size, and their pulmonary artery pressures were analyzed. Results: PH was observed in 85% of patients, especially those with moderate and large PDAs. A strong correlation between ductal size and PH was found. Conclusion: PDA size significantly influences pulmonary artery pressure. Early detection and closure of hemodynamically significant PDA is crucial to prevent vascular remodeling Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 66-68